TINJAUAN KRITIS ZAKEN KABINET DALAM PEMERINTAHAN PRABOWO SUBIANTO TERHADAP STRUKTUR DAN EFEKTIFITAS PEMERINTAHAN SEBAGAI KAJIAN HUKUM TATA NEGARA - Priandana, Nugraha Gading; Wahyudi, Rizky; Fauzani, Najua; Mabilla, Anung (LPPM Universitas Bina Bangsa, 2025)
An effective government structure is essential to achieving good governance as mandated by the constitution. This article examines the concept of Zaken Cabinet as an approach that prioritizes professionalism and competence in governance and its relevance in the context of Indonesia's constitutional law. Referring to Article 17 of the 1945 Constitution and Law No. 39 of 2008, the study explores challenges in implementing the Zaken Cabinet, including political resistance and the need for institutional reform. This approach is believed to enhance governmental efficiency and transparency by reducing political interference in decision-making processes. Through a qualitative methodology based on literature review, the article identifies that the success of a Zaken Cabinet depends on inter-agency coordination, the formulation of a national strategic agenda, and strengthening political support. Therefore, this model presents an innovative solution to address the complexity of governance in Indonesia